Charge‐Reversible Surfactant‐Induced Transformation Between Oil‐in‐Dispersion Emulsions and Pickering Emulsions. (16th April 2021) - Jiang, Jianzhong; Yu, Shijie; Zhang, Wanqing; Zhang, Haojie; Cui, Zhenggang; Xia, Wenshui; Binks, Bernard P.
Abstract: A novel charge‐reversible surfactant, (CH3 )2 N‐(CH2 )10 COONa, was designed and synthesized, which together with silica nanoparticles can stabilize a smart n ‐octane‐in‐water emulsion responsive to pH. At high pH (9.3) the surfactant is anionic carboxylate, which together with the negatively charged silica nanoparticles co‐stabilize flowable oil‐in‐dispersion emulsions, whereas at low pH (4.1) it is turned to cationic form by forming amine salt which can hydrophobize in situ the negatively charged silica nanoparticles to stabilize viscous oil‐in‐water (O/W) Pickering emulsions. At neutral pH (7.5), however, this surfactant is converted to zwitterionic form, which only weakly hydrophobises the silica particles to stabilize O/W Pickering emulsions of large droplet size. Moreover, demulsification can be achieved rapidly triggered by pH. With this strategy particles can be controlled either dispersed in water or adsorbed at the oil‐water interface endowing emulsions with the capacity for intelligent and precise control of stability as well as viscosity and droplet size. Abstract : An emulsion was stabilized by silica particles in combination with a charge‐reversible surfactant, which can be converted between anionic, zwitterionic and cationic forms by pH trigger. Not only can rapid demulsification be achieved, but the emulsion can also be reversibly switched between an oil‐in‐dispersion emulsion and a Pickering emulsion. This strategy endows the emulsion with the capacity for intelligent and precise control of stability as well as viscosity and droplet size.